DECIPHERING THE QUARK-GLUON STRUCTURE OF THE PHOTON IN E-GAMMA COLLISIONS - Eboli, OJP; Gonzalezgarcia, M. C.; Halzen, F.; Novaes, Sérgio Ferraz [UNESP] (Elsevier B.V., 1993)
We investigate the capability of an egamma collider to unravel the hadronic content of the photon. The experimental problem for probing the gluonic structure of the photon is that small-x triggers overwhelmingly select soft photons rather than soft gluons in hard photons. We show that the problem can be finessed in experiments where laser back-scattering is used to prepare a source of very hard photons. We illustrate their power for studying the parton distributions of the photon and, specifically, for separating the quark and gluon components in events where dijets, jet-gamma pairs, and heavy quark pairs are produced.